Comprehensive Analysis of Nasal Polyps Reveals a More Pronounced Type 2 Transcriptomic Profile of Epithelial Cells and Mast Cells in Aspirin-Exacerbated Respiratory Disease - Bangert, Christine; Villazala-Merino, Sergio; Fahrenberger, Martin; Krausgruber, Thomas; Bauer, Wolfgang M.; Stanek, Victoria; Campion, Nicholas James; Bartosik, Tina; Quint, Tamara; Regelsberger, Guenther; Niederberger-Leppin, Verena; Bock, Christoph; et al. (Frontiers in Immunology, 2022)
Chronic rhinosinusitis with nasal polyps is affecting up to 3% of western populations. About 10% of patients with nasal polyps also suffer from asthma and intolerance to aspirin, a syndrome called aspirin-exacerbated respiratory disease. Although eosinophilic inflammation is predominant in polyps of both diseases, phenotypic differences in tissue-derived microenvironment, elucidating disease-specific characteristics, have not yet been identified. We sought to obtain detailed information about phenotypic and transcriptional differences in epithelial and immune cells in polyps of aspirin-tolerant and intolerant patients. Cytokine profiles in nasal secretions and serum of patients suffering from aspirin-exacerbated respiratory disease (n=10) or chronic rhinosinusitis with nasal polyps (n=9) were assessed using a multiplex mesoscale discovery assay. After enrichment for immune cell subsets by flow cytometry, we performed transcriptomic profiling by employing single-cell RNA sequencing. Aspirin-intolerant patients displayed significantly elevated IL-5 and CCL17 levels in nasal secretions corresponding to a more pronounced eosinophilic type 2 inflammation. Transcriptomic profiling revealed that epithelial and mast cells not only complement one another in terms of gene expression associated with the 15-lipoxygenase pathway, but also show a clear type 2 associated inflammatory phenotype as identified by the upregulation of POSTN, CCL26 and IL13 in patients with aspirin-exacerbated respiratory disease. Interestingly, we also observed cellular stress responses indicated by an increase of MTRNR2L12, MTRNR2L8 and NEAT1 across all immune cell subsets in this disease entity. In conclusion, our findings indicate a pivotal role of epithelial and mast cells in the pathogenesis of aspirin-exacerbated respiratory disease.